THE ROLE OF ACTIVITY GAMES IN THE DEVELOPMENT OF CHILDREN WITH HEALTH DEFECTS (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
The article describes the important role of sports and active games in the process of preschool education of children with disabilities . The game, which is an important factor in the physical development of the child, is also considered as a tool of the educational process, as a means of developing the mental and spiritual qualities of the growing person. From this point of view, sports and active play work as a way of correcting and preparing children with disabilities for the most comfortable life in the future and more effective interactions with the social environment. The article shows the specific features of socialization of a child with a health defect, as well as reveals the general and specific tasks of physical education and physical development of children. The importance of the game, in particular mobile, for the entire process of preschool education as a method of comprehensive development of basic skills and abilities of the individual is explained.